Health needs of preschool children. Issue 11 (November 1976) - Bax, M; Hart, H
Abstract : An epidemiological study of disease in a geographically identified population of 250 children is reported. 22% had not seen their general practitioner (GP) at all in the past year, while 20% had seen him four times or more. The vast majority of these visits were because of an infective illness; and developmental and behavioural problems were rarely presented to GPs. 53% of children had not been to hospital since birth, but 11% had been at least four times. Respiratory infections and middle ear disease were the commonest illness reported, and nearly 3% had an infected or discharging ear at the time of examination. 15% of 3 year olds had speech and language problems. 18% of children over 2 years were thought by the examiners to have a behavioural problem, half being assessed as mild, the remainder as moderate or severe.